Problématique générale : Enjeux de l’accessibilité et de l’offre active de sociaux et de santé au sein de la francophonie canadienne en situation minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; Laforge, M.-J. (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette problématique générale vise tout d’abord à présenter un portrait global des communautés francophones en situation minoritaire (CFSM) au Canada. Nous présenterons aussi la problématique de l’accessibilité à des services sociaux et de santé en français en contexte linguistique minoritaire, l’importance de l’accès à des services dans la langue officielle de son choix et les principaux éléments qui justifient le fait d’offrir activement des services sociaux et de santé en français dans les CFSM. Nous établirons également les bases d’une définition de l’offre active et certains contours politiques et historiques qui façonnent les services sociaux et de santé en français en contexte francophone minoritaire. Cette problématique générale sera, par conséquent, une assise pour chacun des chapitres qui composeront cet ouvrage et en facilitera la compréhension.

Active offer, bilingualism, and organizational culture - Vézina, Sylvain (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, the author approaches active offer from the angle of organizational culture. He presents the results of a survey of health professionals working in Anglophone and Francophone hospital facilities in New Brunswick. The organizational culture of these institutions is discussed in light of research in the sociology of organizations, not as a fate but as a construct, as are the rules of the organizational game (hierarchical relations, job description, collective agreements, and so on). The research reveals the predominance of an organizational culture centred on bilingualism, which leads to a persistent confusion between the notions of active offer and bilingualism. From this point of view, although bilingualism is essential to a high-quality active offer in both official languages, it can also be counter-productive when it comes to introducing a culture that is favourable to active offer. The findings show the emphasis placed on bilingualism is often perceived by unilingual people as a threat to the balance of powers within the system, frequently leading to resistance toward any measure favourable to active offer. Hence, the author suggests the value of a culture of active offer should be articulated in terms of the objectives of safety and high-quality care in the official languages. Key words: health professionals, hospital facilities, organizational culture, bilingualism, active offer, New Brunswick.
Chapter 10

Offre active, bilinguisme et culture organisationnelle - Vézina, Sylvain (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce texte, l’auteur aborde l’offre active sous l’angle de la culture organisationnelle. Il y présente les résultats d’une enquête menée auprès de professionnels de la santé oeuvrant au sein d’établissements hospitaliers anglophones et francophones du Nouveau-Brunswick. La culture organisationnelle y est traitée, à la lumière de la sociologie des organisations, non pas comme une fatalité, mais comme un construit, au même titre que les règles du jeu organisationnel (rapports hiérarchiques, définition des tâches, conventions collectives…). Cette recherche fait ressortir la prédominance d’une culture organisationnelle centrée sur le bilinguisme donnant lieu à la persistance d’une confusion entre les notions d’offre active et de bilinguisme. Or, du point de vue de l’auteur, si le bilinguisme est essentiel à l’offre de services de qualité dans les deux langues officielles, il peut être contre-productif quand il s’agit d’introduire une culture favorable à l’offre active. Il affirme, en effet, que l’accent mis sur le bilinguisme est souvent perçu par les personnes unilingues comme une menace à l’équilibre des forces au sein du système entraînant, le plus souvent, de la résistance envers toute mesure favorable à l’offre active. C’est pourquoi il en vient à suggérer la valorisation d’une culture d’offre active autour d’objectifs de sécurité et de qualité des soins dans les langues officielles. Mots-clés : professionnels de la santé, établissements hospitaliers, culture organisationnelle, bilinguisme, offre active, Nouveau-Brunswick
Chapitre 10

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter presents a theoretical framework inspired by strategic analysis, also called the sociology of organizations. By adopting this approach, researchers try to uncover the objectives and strategies used by the actors involved in order to better grasp the dynamics of the system of action, while at the same time taking into consideration the constraints arising from the formal structure. The concepts dealt with include the system of action, power, rules of the game, change, strategy, actor, issue, organization, and environment, all of which take into account the complexity of the challenges surrounding the practice of active offer in health and social services. One of the major contributions of this approach is that it provides an analytical framework making it possible to gain a better comprehension of the relationship between the actor and the system. These two components are essential not only for understanding the subject explored here, but also for identifying the strategies for action used by actors in a given community. Key Words: active offer, social services and health, system of action, power, zone of uncertainty, strategic analysis, sociology of organizations, change, strategy, actor, issue, organization, environment.
Chapter 1

The necessity for normalized tests for speech, language, and hearing assessment of young Francophone children living in linguistic minority settings: Myth or reality? - Lagacé, Josée; Lefebvre, Pascal (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Chapter 13

La nécessité des tests normalisés pour l’évaluation orthophonique et audiologique des jeunes francophones vivant en situation linguistique minoritaire : mythe ou réalité? - Lagacé, Josée; Lefebvre, Pascal (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
La plupart des enfants francophones vivant en situation linguistique minoritaire au Canada sont bilingues. Les audiologistes et les orthophonistes qui effectuent des évaluations pour déterminer si ces derniers présentent des troubles de la communication revendiquent l’élaboration de tests normalisés pour cette population. Pourtant, les pratiques exemplaires proposent des moyens plus efficaces pour déterminer la présence d’un trouble de la communication auprès des enfants bilingues. Ce chapitre recense les données des écrits scientifiques et présente de nouvelles données de recherche démontrant l’écart entre les pratiques exemplaires et les pratiques actuelles liées à l’utilisation de tests normalisés auprès des enfants bilingues en audiologie et en orthophonie. Afin d’améliorer les services pour ces enfants, des recommandations sont formulées pour les programmes universitaires, les programmes de formation continue, les employeurs et les parents. Mots-clés : tests standardisés, tests normalisés, bilinguisme, audiologie, orthophonie, pratiques exemplaires
Chapitre 13

Introduction: Social services and health services in minority-language communities: Towards an understanding of the actors, the system, and the levers of action - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; van Kemenade, Solange (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This introduction provides an overview of Francophone minority communities (CFSM) in Canada, as well as the issue of access to social and health services in French within a linguistic minority context, the importance of access to services in the official language of one’s choice, and the key factors justifying the active provision of social and health services in French within CFSMs. It also lays the groundwork for a definition of active provision and outlines certain political and historical factors that shape social and health services in French within a Francophone minority context. Finally it outlines the book’s common thread, as well as providing an introduction to each of its chapters.

Conclusion: New insights into safe, quality services in official language minority communities - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter we return to the theoretical framework underpinning this volume, the model of strategic analysis that contributes to a better understanding of the role of the actor and the system in making an active offer in the official language of the user’s choice. The chapter addresses the challenges of accessing health and social services in French, the relations among actors within Francophone minority communities, the system and levers of action, as well as strategies to promote active offer of French-language services. More specifically, the main proposals contained in the book are structured around the following six strategies: legal and political levers; strategies to educate and engage future professionals; an organisational culture oriented toward active offer; leadership of social actors and communities; measures to attract and retain bilingual healthcare practitioners; and, finally, mobilisation and collaboration among actors. In conclusion, the strategies are set out as six recommendations in support of the active offer of social and health services in French in a minority context.

Conclusion : des connaissances nouvelles pour des services en français de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire - Bouchard, Pier; Savard, Jacinthe; Savard, Sébastien; Vézina, Sylvain; Drolet, Marie (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Le cadre théorique en filigrane de cet ouvrage, soit le modèle de l’analyse stratégique, est repris la conclusion et contribuer à améliorer la compréhension du rôle de l’acteur et du système dans l’actualisation des principes de l’offre active de services sociaux et de santé dans la langue au choix de l’usager. Le chapitre aborde les enjeux de l'accès à des services sociaux et de santé en français, le jeu des acteurs au sein des communautés francophones en situation minoritaire, le système et les leviers d'action ainsi que les stratégies en faveur de l'offre active. Plus spécificement, on articule les principales propositions contenues dans l’ouvrage autour des six stratégies suivantes : levier juridique et politique, formation et engagement des futurs professionnels, culture organisationnelle axée sur l’offre active, leadership des acteurs sociaux et de la communauté, mesures d’attraction et de rétention des intervenants bilingues, et enfin mobilisation et collaboration des acteurs. En terminant, les stratégies sont énoncées en 6 recommandatons en faveur de l'offre active de services sociaux et de santé en français en contexte minoritaire.

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Chapter 7

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.
Chapitre 7

Behaviours demonstrating active offer: Identification, measurement, and determinants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, we present the behaviours we have identified encouraging and demonstrating the active offer (AO) of social services and health care in French in minority settings, how we measured them, and how we used these measurements to identify the determinants of AO. We will discuss the tools we developed to measure individual AO behaviours, individual perception of organizational support for AO, and personal characteristics that influence AO behaviours (determinants). Various quantitative methods were used to reach our objectives. The results demonstrate that organizational support is the most important determinant of individual AO behaviours. Once controlled for, additional factors included three personal characteristics that increase propensity to demonstrate AO behaviour: education about AO, affirmation of Francophone identity, and competency in French. The sense of competency in English, on the other hand, has a negative association with AO of French-language service. A better understanding of these determinants enables us to refine our strategies to improve the awareness and education of future health and social service professionals on AO. Key Words: active offer behaviours, measurement, determinants, organizational support, individual behaviours, quantitative research.
Chapter 12

Les comportements favorables à l’offre active, leur mesure et leurs déterminants - Savard, Jacinthe; Casimiro, Lynn; Bouchard, Pier; Benoît, Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, nous présenterons comment nous avons répertorié des comportements favorables à une offre active (OA) de services sociaux et de santé en français en contexte minoritaire, comment nous les avons mesurés et comment nous avons utilisé ces mesures pour déceler des déterminants de l’OA. Nous présentons en détail l’élaboration des outils qui ont servi à mesurer les comportements d’OA, le soutien organisationnel perçu envers l’OA et les caractéristiques personnelles qui peuvent influer sur les comportements d’OA (déterminants). Diverses méthodes quantitatives ont été utilisées pour atteindre ces objectifs. Les résultats obtenus démontrent la présence d’un fort lien entre le soutien organisationnel perçu et les comportements individuels d’OA. À soutien organisationnel égal, les caractéristiques individuelles associées à une plus grande propension à démontrer des comportements d’OA incluent une formation sur l’OA, l’affirmation identitaire et la compétence en français. Le sentiment de compétence en anglais est quant à lui associé négativement aux comportements individuels d’OA de services en français. Une meilleure connaissance de ces déterminants permet de raffiner les stratégies de sensibilisation et d’éducation des futurs professionnels de la santé et des services sociaux envers l’OA. Mots-clés : comportements d’offre active, mesure, déterminants, soutien organisationnel, comportements individuels, recherche quantitative.
Chapitre 12

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter describes the experiences of Francophones in eastern Ontario in terms of access to social services and health care. The experiences and perspectives of 40 parents, seniors, and caregivers were collected through semi-structured interviews. Qualitative analysis of the transcripts, as well as visual analysis of the trajectories of a subgroup of nine participants, made it possible to identify facilitators and challenges these users experienced in accessing Frenchlanguage services, either from their perspective or that of their caregivers. More specifically, this chapter emphasizes elements that facilitate access; these are discussed in order to share the lessons learned, which can contribute to improvements in social services and health care in official language minority communities. Key Words: access to services in French, Ontario Francophones, qualitative analysis.
Chapter 6

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.
Chapitre 6

Enjeux et défis dans l’offre de services dans la langue de la minorité : l’expérience des professionnels bilingues dans le réseau de la santé et des services sociaux - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Le présent chapitre dévoile l’expérience de professionnels bilingues quant à l’offre de services sociaux et de santé dans la langue officielle de la minorité en contexte canadien. Soixante-douze professionnels du Manitoba et de l’Est ontarien décrivent les principaux enjeux associés à la langue et les défis auxquels ils sont confrontés quotidiennement dans l’offre active de ces services. Ces défis concernent la pénurie de professionnels et de services bilingues, la difficulté à repérer le client désirant un service dans la langue officielle de la minorité et les professionnels bilingues, ainsi que l’absence d’appui organisationnel pour faire une offre active de services dans les établissements de santé. Pour mieux soutenir l’offre de services dans la langue de la minorité, des pistes de solution sont proposées. Mots-clés : offre active, santé et services sociaux, langue officielle, contexte minoritaire, professionnels.
Chapitre 8

Issues and challenges in providing services in the minority language: The experience of bilingual professionals in the health and social service network - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter explores the experience of bilingual professionals with the provision of health and social services in the official language of minority communities in Canada. Seventy-two professionals from Manitoba and eastern Ontario describe the main issues associated with language access, and the challenges with which they are faced in their day-to-day responsibilities with the active offer of these services. Professionals reported challenges such as shortage of bilingual professionals and services, and difficulty identifying clients who wish for services in the official language of the minority and finding bilingual professionals, as well as lack of organizational support to actively offer services in the minority language in health facilities. Some suggestions to better support the practice of active offer are provided. Key Words: active offer, health and social services, official language, minority communities, professionals.
Chapter 8